High-temperature effects on white cement-based slurry infiltrated fiber concrete with metakaolin and fly ash additive - Aygormez, Yurdakul; Al-mashhadani, Mukhallad M.; Canpolat, Orhan (PONTIFICIA UNIV CATOLICA CHILE, ESCUELA CONSTRUCCION CIVIL, 2020)
In this study, the high flexural parameter properties of Slurry Infiltrated Fiber Concrete (SIFCON) were examined, as was the use of metakaolin and fly ash with PC CEM I 52.5 R (White Cement). 5 series were prepared and metakaolin and fly ash replaced PC CEM I 52.5 R at 25% and 50%. In this study, while researching White Cement in the production of SIFCON samples, metakaolin which is easy to obtain in kaolin-rich soils, and fly ash, which is a waste material, were also evaluated to reduce CO2 emission in cement production. 5% of steel fiber was used in all series and the results of 7 and 28 days flexural and compressive strengths and ultrasonic pulse velocity (UPV) were examined. Given the 28-day test period, a strength increase was observed in metakaolin-added samples, while lower results were obtained in fly ash-added samples since fly ash was not yet completely hydrated. After the 200, 400, and 600 degrees C high-temperature tests, the results of flexural and compressive strengths, UPV, and weight loss were examined. The increase in strength after 300 degrees C can be caused by drying shrinkage of the matrix, whose C-S-H structure is not yet intact, and compression of the fiber wall. The conversion from Ca(OH)(2) to CaO begins at about 400 degrees C, and the C-S-H structure is quickly destroyed as it approaches 600 degrees C. SIFCON samples have the highest mechanical and durability properties by replacing the metakaolin with White Cement by 25%. The lowest results were obtained by replacing the fly ash with White Cement by 50%.
Keywords: SIFCON; metakaolin; fly ash; cement replacement; high temperature; FRACTURE-TOUGHNESS; STRENGTH; PERFORMANCE; DURABILITY; RESISTANCE; HYDRATION; POWDER; Construction & Building Technology; Engineering